Need for psychosocial intervention in an unaccompanied minor diagnosed with lymphoma: A case report - Duran García, Julia; Redondo Elvira, Tamara (Psicooncología, 2023)
Objective: Case of an unaccompanied minor who, after his arrival in Spain, is diagnosed with lymphoma and how an intervention at a psychosocial level is necessary, to first ensure the coverage of basic needs and then address all the psychological symptoms of his situation. Method: An intervention by the area of Social Work and Psycho-Oncology for the management of all the problems associated with the migrant situation and adaptation to the oncological process. Results: At the begginning basic needs (accommodation and food) were coveres and it was ensured access to social and health services, and then psychological intervention started. There is a reduction of anxious symptomatology, managing suicidal ideation and the reduction of negative and depressive thoughts, improving emotional management and enhancing self-control, as well as a better adaptation to the disease situation. Conclusion: The psychosocial approach becomes an indispensable tool for the intervention in people who are in a situation of extreme social vulnerability, who are diagnosed with oncological disease.